An imazethapyr-based herbicide formulation induces genotoxic, biochemical, and individual organizational effects in Leptodactylus latinasus tadpoles (Anura: Leptodactylidae) - Pérez Iglesias, Juan Manuel (2020)
Genotoxic, biochemical, and individual organizational effects on Leptodactylus latinasus tadpoles were evaluated after exposure to an imazethapyr (IMZT)-based commercial herbicide formulation, Pivot® H (10.59% IMZT). A determination of the value of the lethal concentration (LC50) was determined as a toxicological endpoint. Alterations in animal behavior and morphological abnormalities as well as cholinesterase (ChE), catalase (CAT), and glutathione S-transferase (GST) activities were employed as individual sublethal endpoints. Micronuclei frequencies (MNs), binucleated cells (BNs), blebbed nuclei (BLs), lobed nuclei (LBs), notched nuclei (NTs), erythroplastids (EPs), and evaluation of DNA strand breaks were employed as genotoxic endpoints. All biomarkers were evaluated after 48 and 96 h of exposure to concentrations of IMZT within 0.07-4.89 mg/L. LC5096h values of 1.01 and 0.29 mg/L IMZT were obtained for Gosner stages 25 and 36, respectively. Irregular swimming, diamond body shape, and decreased frequency of keratodonts were detected at both sampling times. Results showed that IMZT increased GST activity and MN frequency at 48 and 96 h of exposure. Other nuclear abnormalities were also observed in the circulating erythrocytes of tadpoles, i.e., NT and BL values after 48 h, and LN, BL, and EP values after 96 h. Finally, results showed that IMZT within 0.07-0.22 mg/L increased the genetic damage index in tadpoles exposed for both exposure times (48 and 96 h). This study is the first to report the sublethal biochemical effects of IMZT in anurans and is also the first report using L. latinasus tadpoles as a bioindicator for ecotoxicological studies.